2003
DOI: 10.1249/01.mss.0000078937.22939.7e
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Linkage Scan for Physical Activity Levels in the Quebec Family Study

Abstract: This study identified several chromosomal regions harboring genes that may contribute to the propensity to be physically active or sedentary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 33 publications
1
56
0
2
Order By: Relevance
“…Strong evidence for linkage of plasma leptin levels, one of the most robust markers of fat mass, to this region of chromosome 2 was also seen in a genome-wide scan performed in French obese sibling pairs (6). Other studies have suggested a role for genes in this region in phenotypes such as serum triglycerides (17), blood pressure (18), physical inactivity (19), and type 2 diabetes (20). Association studies of the POMC gene and indexes of adiposity have been inconsistent (21,22), but most have been underpowered.…”
Section: Discussionmentioning
confidence: 75%
“…Strong evidence for linkage of plasma leptin levels, one of the most robust markers of fat mass, to this region of chromosome 2 was also seen in a genome-wide scan performed in French obese sibling pairs (6). Other studies have suggested a role for genes in this region in phenotypes such as serum triglycerides (17), blood pressure (18), physical inactivity (19), and type 2 diabetes (20). Association studies of the POMC gene and indexes of adiposity have been inconsistent (21,22), but most have been underpowered.…”
Section: Discussionmentioning
confidence: 75%
“…The peak on 3q22-q24 was found at the SLC9A9 gene. The region 4q31-q34 overlaps with the region for which suggestive linkages were found in two previous linkage studies for physical fitness (FABP2 gene; Bouchard et al, 2000) and physical activity (UCP1 gene; Simonen et al, 2003). Future association studies should further clarify the possible role of these genes in athlete status.…”
mentioning
confidence: 72%
“…Thus, we can conclude that heredity, to some degree, contributes to the variation in Variability in habitual physical activity EE Wickel and JC Eisenmann PA levels between individuals; however, possibly more important, these results imply that proposed lifestyle strategies aimed at increasing levels of PA need to be different among people. Using the Bouchard activity diary, Simonen et al (2003a) provided additional evidence supporting the role of genetics to partially explain the variation in PA levels among individuals. Three PA phenotypes (inactivity, moderate to strenuous PA, and total daily activity level) derived from the Bouchard diary displayed encouraging linkage evidence for both PA (chromosome 2p22-p16) and IA (chromosomes 7p11.2, 20q13.1).…”
Section: Discussionmentioning
confidence: 99%